STUDENTS’ RESPONSES TOWARD TEACHING READING DESCRIPTIVE TEXTS USING SMALL GROUP DISCUSSION - Widiani, Meida; Apsari, Yanuarti (IKIP Siliwangi, 2022)
This research aimed to describe students’ responses toward teaching reading comprehension of descriptive text using small group discussion. The research used descriptive qualitative. The sample of the research was seventh grade students of one of junior high school in cianjur. The data were obtained from interview and questionnaire. The data analyzed using qualitative descriptive. The result showed that the students’ responses toward teaching reading comprehension of descriptive texts is positive and effective. While, from the questionnaire showed that most students (80%) agree that learning descriptive texts used small group discussion becomes easy to understand the material or the texts, fun/interesting, and enthusiastically for sharing ideas with member of groups. Keywords: Reading, Descriptive Text, Small Group Discussion